THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING APPROACH IN A SECONDARY SCHOOL IN SURABAYA - Ina Christina Shinta; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study is a qualitative study aimed to know the principles of CLT implemented and problems faced by a teacher in an English conversation class of eighth grades in S Secondary School. The data was taken through observation and interview. It was analyzed using Larsen-Freeman’ (2000) and Brown’s (2001) theories and supported by Li (1998) as cited in Ozsevik (2010). The findings revealed that out of sixteen principles, five principles were unachievable, namely using discourse language, being a facilitator, setting social context, having communicative interaction, and producing different utterances. Moreover, the main problem in implementing CLT comes from students’ side, such as students’ low English proficiency, passive style of learning, resistance to participate in communicative classroom activities, and lack of motivation for developing communicative competence. It can be concluded that CLT is a suitable approach in promoting communicative competence for learners as long as the teacher and the students are prepared.